(3TQM cJGH SjHhjgs - (3Ydj Hf YjSi Hf Ydj Hf YHO Gddg, CHh GdMSf GdQeGfj , J (B384 (3g`s; (3YeQh Hf YKeGf Hf bfHQ GdMGQKj HGdhdGA, CHh HTQ, GdedbH SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3jHJOF Hbhdg hdG JLhR gPg GdeHGdZI EdG HGdEVGaI dGeQjf CMOgeG WdH GdCYQa ai GdeYfi GdfGOQ (B( (3ef HGH GdeaYhd GdeWdb(B) s
(3BNQgG (B:s
(3hjfJgi (B" (3HHGH JQNje eG jQO Edjg HYO GdMPa MQa (B" (3ef HGH GdJQNje (B" s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
Keywords: (3GdfMhs